Conventional supine delivery position versus free-position delivery guidance intervention on delivery outcomes, pain, and maternal–neonatal outcomes in primiparous women - Suyu Zhang; Zhijing He; Zhizhong Wang (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This randomized comparative study investigated the effects of free-position delivery guidance combined with prenatal intervention on pain levels, delivery outcomes, and maternal–neonatal outcomes in primiparous women. A total of 80 primiparous women admitted to the hospital between April 2023 and October 2025 were included in the study. Participants were randomly divided into two groups of 40 each using a random number table. The control group received conventional supine delivery with basic guidance, while the study group received free position delivery guidance combined with prenatal intervention. Labor duration, pain scores, delivery outcomes, and the incidence of adverse maternal–neonatal outcomes were compared between the two groups. The study group showed significantly shorter labor duration and total labor time compared to the control group (P<0.05). The study group also demonstrated significantly lower pain scores (P<0.05). The study group exhibited a significantly higher rate of natural delivery and a significantly lower rate of cesarean section compared to the control group (P<0.05). The incidence of adverse maternal-infant outcomes in the study group was significantly lower than that in the control group (P<0.05). The combination of free-position delivery guidance and prenatal intervention can effectively improve delivery outcomes, alleviate labor pain, and reduce adverse maternal–neonatal outcomes in primiparous women.